Assessment of the effects of employees job satisfaction on work performance in insurance company: A case of Jubilee insurance company - Mahene, Esther John (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment for the requirements of the award of Master of Business Administration Degree of Mzumbe University.